History, Policy and Public Purpose - Green, Alix R. author. aut Link
IX, 146 p.
Keywords: This book takes a fresh look at the connection between history and policy, proposing that historians rediscover a sense of ‘public purpose’ that can embrace political decision-making – and also enhance historical practice. Making policy is a complex and messy affair, calling on many different forms of expertise and historians have often been reluctant to get involved in policy advice, with those interested in ‘history in public’ tending to work with museums, heritage sites, broadcasters and community organisations. Green notes, however, that historians have also insisted that ‘history matters’ in public policy debate, and been critical of politicians’ distortions or neglect of the past. She argues that it is not possible to have it both ways. Alix Green is Lecturer in Public History at the University of Central Lancashire, UK. She read history at the University of Cambridge and spent ten years in policy research and government relations before bringing her experience into academic research on the uses of history. She is particularly interested in historical thinking and the international and conceptual aspects of public history.